2018
DOI: 10.3389/fnins.2018.00779
|View full text |Cite
|
Sign up to set email alerts
|

Things Become Appealing When I Win: Neural Evidence of the Influence of Competition Outcomes on Brand Preference

Abstract: Against the background of an increasingly competitive market environment, the current study aimed to investigate whether and how victory and defeat, as two critical factors in competition outcomes, would affect consumers’ preference of unfamiliar brands. In the experiment, participants’ status of victory or defeat was induced by a pseudo-online game, followed by a main task of brand preference rating. Using the precise and intuitive attributes of neuroscientific techniques, we adopted event-related potentials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
0
10
0
12
Order By: Relevance
“…The time windows of N100 and P200 were 160-210 and 210-270 ms after onset, respectively. The nine electrodes were collected because it has been proven and is widely accepted that both N100 (Yu et al, 2018) and P200 (Wang et al, 2012) can usually be found in the frontal-central area. Then, two media channels (traditional newspaper/internet news portal) × 2 news categories (hard news/soft news) × 9 electrodes (F1/z/2, FC1/z/2, C1/z/2) ANOVAs were performed for the N100 and P200.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time windows of N100 and P200 were 160-210 and 210-270 ms after onset, respectively. The nine electrodes were collected because it has been proven and is widely accepted that both N100 (Yu et al, 2018) and P200 (Wang et al, 2012) can usually be found in the frontal-central area. Then, two media channels (traditional newspaper/internet news portal) × 2 news categories (hard news/soft news) × 9 electrodes (F1/z/2, FC1/z/2, C1/z/2) ANOVAs were performed for the N100 and P200.…”
Section: Discussionmentioning
confidence: 99%
“…N100 is an early negative ERP component induced by emotional information, which reaches its peak at ∼130-150 ms after the onset of an emotional stimulus at frontal-central sites (Yu et al, 2018). According to previous studies, N1 is considered to be an index of affective arousal (Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As all the stimulus materials contained some kind of loss, subjects had to take more factors into consideration. Previous ERP studies demonstrated that the frontal P200 component appeared in the early stage of cognitive decision-making and that it was related to the initial assessment of stimulus and the rapid emotional feedback (Huang and Luo, 2006; Potts et al, 2006; Nikolaev et al, 2008; Boudreau et al, 2009; Yu et al, 2018). While making intertemporal decisions, the amplitude of the P200 component of the SS options was significantly smaller than that of the LL options, indicating an unconscious increased attention when choosing the LL options.…”
Section: Discussionmentioning
confidence: 99%
“…The first part of the experiment was a time-estimation game (Yu et al, 2018). When the participants entered the laboratory, they were instructed to compete with participants as the opponents in FIGURE 1 | Experimental procedure.…”
Section: Time-estimation Gamementioning
confidence: 99%